1969
DOI: 10.1002/neu.480010305
|View full text |Cite
|
Sign up to set email alerts
|

The turnover of phosphatidyl choline in rat cerebral cortex membranes in vivo

Abstract: SUMMARYThe incorporation of choline administered by intraventricular injection in uivo into the phosphatidyl choline of the membranes of rat cerebral cortex was studied, and it was demonstrated that the radioactive choline was incorporated almost exclusively into phosphatidyl choline in each of the fractions. The various membranous fractions had different half-lives of phosphatidyl choline. The half-life of the phosphatidyl choline of myelin was 167 days, the longest of any fraction, while the value of 27 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…More recently, Friede and Samorajski (21) and Webster (54) have done careful morphological investigations which suggest that growth of the myelin sheath occurs at the region of the outer mesaxon. Biochemical studies of lecithin metabolism in brain (28,31,50) and tissue culture (27) have indicated that myelin metabolism of this component does not cease in the adult. The studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Friede and Samorajski (21) and Webster (54) have done careful morphological investigations which suggest that growth of the myelin sheath occurs at the region of the outer mesaxon. Biochemical studies of lecithin metabolism in brain (28,31,50) and tissue culture (27) have indicated that myelin metabolism of this component does not cease in the adult. The studies.…”
Section: Discussionmentioning
confidence: 99%
“…The radioactivity recovered from the supernate as phosphorylcholine, choline, or acetylcholine plus that solubilized from the pellet by chloroform-methanol accounted for 92% of the total radioactivity present in the homogenate . Previous data in a variety of neural tissues indicate that most of the choline present in the phospholipid pathway after briefexposure to [''H]choline is in the form of phosphorylcholine or phosphatidylcholine (10,20,46,48). That this was the case for the rabbit retina was confirmed in retinas where a chloroformmethanol extract of the pellet was prepared according to Folch et al (28) and analyzed by thin-layer chromatography on silica gel in 95 :36:6 chloroform : methanol :water according to Flower and Blackwell (27) .…”
Section: Chemical Analysismentioning
confidence: 99%
“…Although brain lipids may be labeled in vivo by many types of precursors, the information gained is influenced by the choice of precursors. The use of choline (10,11) or ethanolamine (12,13) as precursors is restricted to comparisons of subclasses of the respective phosphoglycerides. Acetate and glucose ( 14,15) are incorporated not only into all lipid classes but also into all moieties of the lipid molecules.…”
Section: Introductionmentioning
confidence: 99%